UK Competition Policy and Shareholder Value: The Impact of Merger Inquiries - Arnold, Malcolm F.; Parker, David (Blackwell Publishing, 2007)
Some previous studies have suggested that competition re´gimes can destroy shareholder value. This study examines data on 50 mergers in the UK between 1989 and 2002. The study confirms the finding from earlier studies of greater gains to shareholders in target than bidding companies, but does not find evidence supporting overall loss of shareholder value to target company shareholders when a merger is prohibited. It finds evidence that when the regulatory re´gime is stable and well understood the capital market behaves efficiently in response to new information. However, for a subgroup of the mergers involving companies with a new regulatory re´gime, where the industry and the stock market had little or no experience with respect to mergers, the capital market operated less efficiently.